PENGARUH PEMBERIAN BISKUIT BEKATUL (RICE BRAND) TERHADAP INDEKS MASA TUBUH PENDERITA OBSESITAS - Dirga Dirga; Atika Dalili Akhmad; Sudewi Mukaromah K; Nur Adliani; Sukrasno Sukrasno (Jurnal Farmasi Malahayati, 2019)
The prevalence of an obesity patient in Indonesia for adult (more than 18 years old) is increasing every year. It is strongly suggested to ameliorate the eating habits and increase the physic activities as the best way to transmute the risky prime factor for the cause of degenerative disease. The utilizing of Rice Bran as a traditional medicine can be also made used as an ingredient of food. Rice Bran can be modified as a simple and instant food in a form of an appealing biscuit which has a good taste and high nutrition. The aim of this Rice bran biscuit research is to find out the optimal formulation of rice bran biscuit which is appropriate to the national standard of biscuit production, and it is also expected to bring affection towards the weight dropping for the obesity patient. The utilized method in this research is a quasi experimental research. The sample used in this study is obese people who meet the criteria of inclusion, They are divided into two groups; a. control group. b. experimental group. The results showed that the best biscuits physical chemical parameters have characteristic fat content 9.58%, ash content 3.16%, crude fiber 6.02%, broken power 12.57 N, color 4.82 (neutral), taste 4.43 (somewhat dislike), flavour 1.90 (somewhat dislike). While the best biscuits organoleptic parameters have characteristic fat content 7.88%, ash content 4.26%, crude fiber 3.89%, broken power 4.44 N, color 5.80 (rather like), taste 3.88 (rather like), flavour 2.44 (somewhat dislike). While on testing Effect of biscuits bekatul on IMT on obese patients found that there are differences of IMT obese patients before and after consuming rice bran biscuit for 1 month in the form of decreased BMI average 0.63 kg / m2 with value p = 0.001 (p <0.05 ).